Nano-Confined Solar-Thermal Water Purification Boosted by Physical Field Disturbance Coupled with Ultrafast Non-Radical Advanced Oxidation Process - Jiao, Fan‑Zhen; Fang, Xiaoyang; Hou, Sheng‑Xing; Wang, Zhi‑Hao; You, Wenbo; Yang, Zhenzhong; Yu, Zhong‑Zhen; Qu, Jin (Nano-Micro Letters, 2026)
Solar interfacial evaporation has undergone rapid development in recent years, yet its overall performance has reached a plateau due to limited advances in solar-thermal materials. Herein, we propose a synergistic nano-confinement and physical-field–modulation strategy that enables concurrent acceleration of solar-driven evaporation of water and on-site remediation of organic pollutants. Implemented in hollow mesoporous carbon nanocages integrated with Fe–N4 catalytic sites and inner wall plasmonic Au nanoparticles, the system couples mesoporous confinement with localized thermal and pressure perturbations to transform bulk water into thermodynamically activated intermediate states and substantially reduce the effective vaporization enthalpy. This integrated framework delivers high evaporation rates of 2.56 kg m−2 h−1 in planar devices and 6.84 kg m−2 h−1 in 3D architectures under one-sun irradiation, with a kinetic enhanced Hertz–Knudsen–Schrage–derived evaporation coefficient. Simultaneously, the Fe–N4 sites enable non-radical peroxymonosulfate activation for ultrafast degradation of bisphenol A, achieving a rate of 182.5 L g−1 min−1. This work establishes an ingenious strategy for coupling water-state regulation and catalytic pollutant degradation to break the performance bottleneck of solar-thermal purification. Highlights: 1 Synergistic nano-confinement and physical field modulation thermodynamically activate water and accelerate solar-driven evaporation, achieving high rates up to 6.84 kg m−2 h−1 under one-sun irradiation. 2 The hollow nanocage architecture with highly accessible Fe–N4 sites enables non-radical peroxymonosulfate activation, delivering ultrafast bisphenol A degradation with a mass-normalized rate constant of 182.5 L g−1 min−1. 3 Concurrent acceleration of solar-driven evaporation of water and on-site remediation of organic pollutants is achieved.